Bypassing the gatekeeper: incidental negative cues stimulate choices with negative outcomes. Issue 5 (4th July 2019) - Strohmaier, Niek; Veling, Harm
ABSTRACT: The Theory of Event Coding (TEC) predicts that exposure to affective cues can automatically trigger affectively congruent behaviour due to shared representational codes. An intriguing hypothesis from this theory is that exposure to aversive cues can automatically trigger actions that have previously been learned to result in aversive outcomes. Previous work has indeed found such a compatibility effect on reaction times in forced-choice tasks, but not for action selection in free-choice tasks. Failure to observe this compatibility effect for aversive cues in free choice tasks suggests that control processes aimed at directing behaviour toward positive outcomes may overrule the automatic activation of affectively congruent responses in case of aversive cues. The present study tested whether minimising such control could cause selection of actions that have been learned to result in aversive outcomes. Results showed incidental exposure to aversive cues biased selection of behaviours with learned aversive outcomes over behaviours with positive outcomes, despite a preference to execute the positive- over the negative-outcome actions evidenced by a separate behaviour measurement and self-reports. These results suggest motivational processes to select actions with positive consequences may sometimes be bypassed. Data and Materials: http://doi.org/10.17605/osf.io/ym7qu